Light extraction enhancement of SOI-based erbium/oxygen Co-implanted photonic crystal microcavities - 张家顺 王玥 吴远大 张晓光 姜婷 安俊明 李建光 王红杰 胡雄伟 (Journal of semiconductors, 2011)
H_5 photonic crystal（PC） microcavities co-implanted with erbium（Er） and oxygen（O） ions were fabricated on silicon-on-insulator（SOI） wafers.Photoluminescence（PL） measurements were taken at room temperature and a light extraction enhancement of up to 12 was obtained at 1.54μm,as compared to an identically implanted unpatterned SOI wafer.In addition,we also explored the adjustment of cavity modes by changing the structural parameters of the PC,and the measured results showed that the cavity-resonant peaks shifted towards shorter wavelengths as the radius of the air holes increased,which is consistent with the theoretical simulation.